(untitled) (Journal of Engineering and Health Sciences, 2022)
Management of boarding institutions of the University are important to extend the lifecycle of the building and reduce the loss of the company. When a university hostel is neglected, a defect may occur which may result in extensive and inevitable damage to the fabric of the building or structure. The objective of this study is to host a University Institution in Malaysia to find a maintenance problem that uses the snapshot model to determine the major predominant mistakes, causes of mistakes, prevention and analysis of consequences. Defects and problem faces will be collected and recorded in the check list. This will be done by questionnaire and distributed to all service users at the hostel management student hostel University Institution. Therefore, this paper focuses on the management of boarding Universities that use the snapshot model to identify and define major predominant errors, causes of errors, prevention and impact analysis that are aimed at reducing downtime of plant items by taking into account the possible effects of failure in terms of cost. Analysis shows that the Hostel building contributed to the most problematic areas in the dormitory of the Islamic University Institution based on the snapshot model is a kind of hierarchical analysis